Mock meat, masculinity, and redemption narratives: vegan men's negotiations and performances of gender and eating. - Oliver, Catherine (Social Movement Studies, 2023)
Veganism's visibility has soared in recent years. Contemporary veganism has built a trident approach of outreach that emphasises health benefits, ethical concerns about animals, and environmentally sustainable consumption. With this growth, there have been opportunities for influencer-activists to profit from positioning themselves as movement leaders. This is often connected with thin, white, wealthy women and the wellness industry, but there is also a changing 'meatless masculinity' within vegan influencer-activist spaces. Hegemonic ideals of masculinity around physical strength and virility are being hyper-individualised to 'sell' veganism through embodied and cultural performances of 'redemption narratives' by vegan influencer-activist men. However, in interviews with vegan men in Britain, their relation to these meatless masculinities was found to be in tension with hegemonic masculinity. Interviewees instead related their veganism to an ungoverning of masculine bodily ideals. Veganism was revealed in the interviews as entangled with men representing themselves as part of a progressive masculinity that engages with feminist ideas, even if they are sometimes misunderstood. In this paper, I explore the prevalence and purpose of these masculinity narratives online through social media examples, before exploring a contradictory growth in the re-thinking and rejection of hegemonic masculinity within the vegan constituency through interviews. I conclude that while vegan masculinities offer the potential for men to be a little less governed by gendered norms there remains a need for vegans to more fully embrace a feminist and intersectional veganism that is not dominated by whiteness and masculinist ideals.